Chie in kebaya Catatan inspiratif untuk tampil anggun berkebaya Ria Pentasari;editor, Wicahyaning Putri, Theresia Vini S - PENTASARI, Ria; Vini S, Theresia; Putri, Wicahyaning (2008)
128 hlm ilus 22 cm